Pengaruh Kualitas Pelayanan dan Motivasi Pelayanan Publik terhaap Kepuasan Masyarakat pada Terminal Tipe A Kiliran Jao - Sepsi Indrawati; Heliyani Heliyani (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
This study aims to determine the effect of service quality and public service motivation on community satisfaction on employees of Terminal Type A Kiliran Jao. The method used in this research is quantitative research with a descriptive approach. The population in this study were employees at Terminal Type A Kiliran Jao. The sample used was 84 people using a saturated sampling technique (census). The data analysis technique is multiple linear regression. The results of the study show that: (1) Service quality has a positive and significant effect on community satisfaction. (2) Public service motivation has a positive and significant effect on community satisfaction. (3) Quality of service and motivation of public services together have a positive and significant effect on community satisfaction in Terminal Type A Kiliran Jao.